2013
DOI: 10.3791/50323
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Macrophage Polarization Using Bone Marrow Derived Macrophages

Abstract: The article describes a readily easy adaptive in vitro model to investigate macrophage polarization. In the presence of GM-CSF/M-CSF, hematopoietic stem/progenitor cells from the bone marrow are directed into monocytic differentiation, followed by M1 or M2 stimulation. The activation status can be tracked by changes in cell surface antigens, gene expression and cell signaling pathways. Video LinkThe video component of this article can be found at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
205
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 238 publications
(214 citation statements)
references
References 21 publications
7
205
0
2
Order By: Relevance
“…1 A and B). Monocytes from the bone marrow of healthy mice were isolated, cultivated in vitro, and polarized into M1-or M2-like macrophages using chemokine mixtures (25). We found that the two macrophage subtypes phagocytosed particles to a similar degree (Fig.…”
Section: Methodsmentioning
confidence: 74%
“…1 A and B). Monocytes from the bone marrow of healthy mice were isolated, cultivated in vitro, and polarized into M1-or M2-like macrophages using chemokine mixtures (25). We found that the two macrophage subtypes phagocytosed particles to a similar degree (Fig.…”
Section: Methodsmentioning
confidence: 74%
“…Bone marrow macrophages were isolated from the femur and tibia of 14-day-old C57Bl/6 mice, cultured them in 15-cm dishes in RPMI 1640 supplemented with 10% heat-inactivated fetal bovine serum, 100 U/ml penicillin, 100 μg/ml streptomycin, 2 mM L-glutamine, 10 mM Hepes (all Gibco, Invitrogen) and 15% L-929 cell-conditioned medium (LCM) containing M-CSF for 8 days, then induced their differentiation toward an intestinal M2 phenotype by treating for 24 h with IL-4 (20 ng/ml, Peprotech) and IL-10 (10 ng/ml, R&D Systems). Flow cytometry was then performed to assure the intestinal (M2) phenotype using markers for CD206 and CD163 [13]. Cocultured enteroids with niche components performed on three separate experiments with at least ten different enteroids evaluated per experimental group.…”
Section: Methodsmentioning
confidence: 99%
“…With respect to macrophages, we cocultured WT ATB2s or Ltb4r1KO ATB2s with WT BM-derived macrophages (BMDMs) that had been stimulated with either LPS or IL-4/IL-13 to produce an M1-like or M2-like polarization state, respectively (42,43). WT ATB2s had a greater effect in stimulating CD69 expression in M1-like BMDMs compared with Ltb4r1KO ATB2s (Figure 5D) accompanied by greater production of the proinflammatory cytokines Tnfa, Il6, and Il1b ( Figure 5E).…”
Section: Cd5mentioning
confidence: 99%